The Hop Polyphenols Xanthohumol and 8-Prenyl-Naringenin Antagonize the Estrogenic Effects of Fusarium Mycotoxins in Human Endometrial Cancer Cells - Aichinger, Georg; Beisl, Julia; Marko, Doris (Frontiers in Nutrition, 2018)
The Fusarium toxin zearalenone (ZEN) and its reductive metabolite α-zearalenol (α-ZEL) are well-documented endocrine disruptors that are frequently found to contaminate cereal products, including beer. But also hop is known to represent a source for endocrine active compounds, containing amongst others xanthohumol (XAN), which might be converted to the potent phytoestrogen 8-prenylnaringenin (8-PN). In the present study, we investigated the interaction of these xenoestrogens in mixtures which might occur in beer. Estrogenicity was measured as induction of alkaline phosphatase (AlP) expression in estrogen-sensitive Ishikawa cells. In binary combinations, XAN was found to act as a potent antagonist of mycotoxin-induced estrogenicity, significantly suppressing the AlP-inducing impact of both ZEN and α-ZEL at nanomolar concentrations. Also 8-PN antagonized the estrogenic stimulus of the two fungal metabolites, although less pronounced. These effects also manifested in combinations of three or four test compounds, and at the level of cell proliferation, that was assessed via an E-screen-like approach in Ishikawa cells. Of note, co-exposure to the investigated myco- and phytoestrogens did not result in additive or overadditive/synergistic estrogenic effects in the applied test system. Being aware that the actual study is still limited to the in vitro situation, our results even suggest that prenylated chalkones from hops might protect against Fusarium toxin–induced endocrine disruptive activities at concentrations that can be reached by moderate beer consumption.